1997
DOI: 10.1152/ajpheart.1997.272.1.h392
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and diffusional permeabilities of isolated outer medullary descending vasa recta from the rat

Abstract: Water permeates many microvessel walls via a pathway shared with small hydrophilic solutes and also via an exclusive water pathway. In outer medullary descending vasa recta (OMDVR), the relationship between diffusional permeabilities to water and sodium indicates the existence of an exclusive water pathway and suggests that of a shared pathway. We investigated the latter possibility by estimating hydraulic permeability (Lp) and diffusional permeability to [3H]raffinose (P(raf)) in isolated, perfused OMDVR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…In the control group, fluorescence declines due to leakage of DAF-2 from the cytoplasm. Fluorescence is greater on exposure to BK (100 nM) and increases further when the bath contains the superoxide dismutase mimetic tempol (1 mM diffusive transport of NaCl and other small hydrophilic solutes (82,109,158). In addition to this, transcellular pathways have been identified that conduct transport of urea and water (51, 52, 92, 93, 97-99, 106, 108, 117, 118).…”
Section: Transport Of Solutes and Water Across Vasa Rectamentioning
confidence: 99%
“…In the control group, fluorescence declines due to leakage of DAF-2 from the cytoplasm. Fluorescence is greater on exposure to BK (100 nM) and increases further when the bath contains the superoxide dismutase mimetic tempol (1 mM diffusive transport of NaCl and other small hydrophilic solutes (82,109,158). In addition to this, transcellular pathways have been identified that conduct transport of urea and water (51, 52, 92, 93, 97-99, 106, 108, 117, 118).…”
Section: Transport Of Solutes and Water Across Vasa Rectamentioning
confidence: 99%
“…As will be discussed in subsequent sections, transport of water across the DVR wall is more rigorously described by simulating parallel pathways. One pathway is the highly selective AQP1 molecule ( ss ϭ 1.0) and a parallel pathway that conducts both water movement as well as convective and diffusive flux of small solutes ( ss Ϸ 0) (77,87,89,95,135). Expression of AQP1 in DVR has been hypothesized to play an important role in the optimization of renal medullary countercurrent exchanger function (87).…”
Section: Countercurrent Exchange-general Concepts and Evolution Of Unmentioning
confidence: 99%
“…Water moves through the walls of DVR via pathways of at least two kinds (77,89,90,135). Analysis of the permeabilities of DVR indicates that a "shared" transmural pathway for water and hydrophilic solutes exists in parallel with a "water only" pathway ( Ϸ 1.0) that excludes hydrophilic solutes.…”
Section: Transport Of Water Through the Dvr Wallmentioning
confidence: 99%
“…In the case of renal microvessels, where outer medullary descending vasa recta have been microdissected and perfused in vitro, osmotic water permeability driven by small solutes is very high (P f ∼0.11 cm/s) and has been attributed to transcellular water movement through AQP1 water channels (36). In response to oncotic driving forces (albumin gradients), vasa recta P f (assuming a unity albumin reflection coefficient) was ∼1 cm/s, suggesting a high paracellular water permeability involving wide pores (37). The data in this study suggest a different situation in lung microvessels, where AQP1-dependent transcellular water movement is most important.…”
Section: Figurementioning
confidence: 99%